2015
DOI: 10.1093/brain/awv200
|View full text |Cite
|
Sign up to set email alerts
|

Coherent neural oscillations predict future motor and language improvement after stroke

Abstract: Recent findings have demonstrated that stroke lesions affect neural communication in the entire brain. However, it is less clear whether network interactions are also relevant for plasticity and repair. This study investigated whether the coherence of neural oscillations at language or motor nodes is associated with future clinical improvement. Twenty-four stroke patients underwent high-density EEG recordings and standardized motor and language tests at 2-3 weeks (T0) and 3 months (T1) after stroke onset. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
141
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(156 citation statements)
references
References 87 publications
8
141
0
1
Order By: Relevance
“…In many cases, these plastic changes did not translate into functional gains. Nonetheless, research using tMS, fMRI, positron emission tomography (PET), or other novel tools such as high-density array EEG [90, 91] to understand how rehabilitation changes brain function after stroke is of great value in advancing the scientific underpinnings of the field and may aid in designing successful trials.…”
Section: Commentarymentioning
confidence: 99%
“…In many cases, these plastic changes did not translate into functional gains. Nonetheless, research using tMS, fMRI, positron emission tomography (PET), or other novel tools such as high-density array EEG [90, 91] to understand how rehabilitation changes brain function after stroke is of great value in advancing the scientific underpinnings of the field and may aid in designing successful trials.…”
Section: Commentarymentioning
confidence: 99%
“…EEG measures of coherence or phase and amplitude consistency of neural oscillations between two brain regions may function as additional probes of those processes evaluated with resting-state fMRI functional connectivity analyses as above [145, 146]. Dubovik et al [147] found greater disruption of functional connectivity in the alpha frequency band in individuals with stroke relative to healthy controls.…”
Section: Spontaneous Mechanisms Of Functional Recoverymentioning
confidence: 99%
“…Additional work is warranted to substantiate these findings. Other examples of potential stroke biomarkers include total infarct volume [195], white matter tract injury [2022, 138, 196], cortical activation [42, 52, 91, 175, 138, 197, 198] and connectivity [139, 137, 145, 147, 177, 138, 199], and genetic polymorphisms derived from simple blood tests [15, 16, 200]. These measures may serve an important role in guiding treatment, stratifying subjects in intervention studies, and ultimately predicting functional outcome and response to therapy.…”
Section: The Role Of Biomarkersmentioning
confidence: 99%
“…Similarly, neuroplasticity indexed by spectral and evoked potential changes in working memory and attention has been observed after strokes in lateral frontal cortex (Voytek et al 2010). The potential of such neuronal oscillations as biomarkers for monitoring neurorehabilitation and recovery of language function is largely unexplored (e.g., Kielar et al 2016; Meltzer et al 2013; Nicolo et al, 2015; Spironelli & Angrilli, 2009; Spironelli et al 2013). …”
Section: Introductionmentioning
confidence: 99%